The Effects of Consumption L-Arabinose on Metabolic Syndrome in Humans - Ziming,; Dianpeng Li,; Haiying Jiang,; Guiyun Qian,; Weiguo Sui,; Guimian Zou,; Hourui Zhang, (Journal of Pharmacy and Nutrition Sciences, 2013)
On the basis of results in rat, L-arabinose decreased total cholesterol (TC), triglycerides (TG), fasting glucose, systolic blood pressure, increased high-density lipoprotein cholesterol (HDLC), and enhanced the glucose tolerance. The primary purposes of the present study was to determine the effects of consumption L-arabinose on metabolic syndrome in humans.All volunteers received L-Arabinose by dissolving it in water. The volunteers didn’t change the diet habits and lifestyles during the whole experiment. The trial lasted for 6 months, and experimental indicators were assayed every two months, which including weight, waist circumference, blood pressure, TG, TC, HDLC, low-density lipoprotein cholesterol (LDLC), fasting plasma glucose, erum uric acid, serum creatinine (Scr), bloodurea nitrogen (BUN), alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Our results showed that the L-arabinose decreased waist circumference, TC, fasting glucose, serum uric acid, ALT and slightly increased HDLCand slightly decreased diastolic blood pressure after 6 months. A tendency for decreased waist circumference, TC, fasting glucose, serum uric acid, ALT after 2, 4 and 6 months of treatment with L-arabinose was observed. In addition, L-arabinose decreased TC, LDLC and body weight. No effects on Scr, BUN, AST. In conclusions, L-arabinosewould reduce most the metabolic syndrome risk factors(decreased circumference, TC, fasting glucose, and so on), and treat the metabolic syndrome as a whole.The present study would provides strong evidence that long-term received L-arabinose would be manage metabolic syndrome.